Elleanthus albiflorus (Orchidaceae) a new, white-flowered species from Peru - Dudek, Magdalena; Baranow, Przemysław; Kolanowska, Marta; Rykaczewski, Max (Phytotaxa, 2017)
Elleanthus albiflorus (Orchidaceae) is described and illustrated based on Peruvian material. The novelty resembles E. flavescens from which it can be easily distinguished by the white flowers, flabellate lip and presence of lip calli with prominent outgrows. A key for identification of all Peruvian species of Elleanthus with branching stems is provided.